Atoll Reef Geomorphology of Sagori Island, SE Sulawesi: A Reconnaissance Study - Tubagus Solihuddin (Geological Agency, 2017)
DOI: 10.17014/ijog.4.3.181-191The Sagori Atoll of the Kabaena Island, SE Sulawesi is one of Indonesia’s remote tropical reefs and such has received little attention from reef researchers. Non of early scientific expeditions reported either geomorphology or ecology of the Sagori Atoll in detail. This study is the first investigation of the reef geomorphology and associated habitats of Sagori Atoll within a biodiversity of “Coral reef Triangle Initiative - CTI” region, using data from satellite imagery and on ground observation. The Sagori Atoll environment consists of reef-island, atoll rim, and lagoon in which six habitats are associated, including: sand cay, coralgal pavement, sand sheet (intertidal and subtidal), sand-hardground striation, and outer atoll rim and lagoon (shallow and deep). The reef-island is built from sediments that are entirely calcareous, resting on a platform of lithified coral conglomerate. The atoll rim is dominated by coralgal pavement consisting mainly of both encrusting and living coralline algae. The lagoon which is a semi-enclosed pool and opens to the eastern side, consists of sand and scattered corals. The atoll formation is considered to be of nonvolcanic origin, but is rising from the depth of due to anticlinal island subsidence.